(untitled) (Eurasian Journal of History, Geography and Economics, 2022)
This article discusses ways to improve risk assessment methods in commercial banks. It also analyzes the most diverse risk positions to ensure maximum diversification, which is the process of collecting different loans, so that borrowers do not have changes in the external economic environment in which they operate. In addition, conclusions and recommendations were made on how to improve risk assessment in commercial banks.